The initial material and the achievements in winter durum wheat breeding in a content of carotenoids in the grain of FSBSI “ARC “Donskoy” - D. P. Dorokhova; M. M. Kopus (Зерновое хозяйство России, 2018)
The initial material and the achievements in winter durum wheat breeding in a content of carotenoids in the grain of FSBSI “ARC “Donskoy” The carotenoids of winter durum wheat are of great importance for their consumption; they color flour and grain products (pasta, spaghetti, cereals, semolina, couscous, ravioli, etc.) in yellow. Besides, they are a source of vitamin A. The content of carotenoids in grain depends on both hereditary (genetic) and non-hereditary (phenotypic) factors. Out work deals with the characteristics of commercial, promising and breeding variety samples of winter durum wheat selected by the FSBSI “ARC “Donskoy” compared with the varieties selected in other regions. The material for research was the grain (oilcake) of the varieties cultivated in interstation (IsVt) and competitive (CVt-1) variety testings in 2014-2016. Protein and gluten content in grain has been measured by SpectraStar-2200, carotenoids have been determined by the Sozinov and Zhukova’s method (1967) with additions and changes by the biochemical laboratory. The study showed that the variety “Donchanka” possessed the highest index of carotenoids with variability of 68Mg%. The promising and breeding samples are similar to or slightly inferior to standard. At the same time the local variety “Novinka 5” and the varieties “Winter Gold” and “Karavella” of other regions significantly surpass the standard variety in carotenoids. Importantly, the large content of carotenoids in grain doesn’t reduce protein and gluten content in grain; they have an effect only on the grade of purchased marketable grain.